Anodic stripping voltammetry of sulphide at a nickel film: towards the development of a reagentless sensor. - Giovanelli, D; Lawrence, N; Wilkins, S; Jiang, L; Jones, T; Compton, R (2003)
The determination of sulphide at an electrochemically generated nickel oxide layer at glassy carbon and screen-printed electrodes in acidic media has been examined and appraised. The NiO layer was found to produce a stripping-like signal to sulphide and gave a linear peak current response from 20 to 90 muM. The response was further enhanced by repetitive cycling allowing accumulation of nickel sulphide at the electrode surface such that lower micromolar levels of sulphide (i.e. 5 muM) can be determined. The response at the NiO layer to sulphide is shown to be reproducible over a period of 24 h, thereby offering the development of a disposable amperometric sensor for sulphide.